A Boundary Integral Method for Computing Elastic Moment Tensors for Ellipses and Ellipsoids (Journal of Computational Mathematics, 2018)
The concept of elastic moment tensor occurs in several interesting contexts, in particular in imaging small elastic inclusions and in asymptotic models of dilute elastic composites. In this paper, we compute the elastic moment tensors for ellipses and ellipsoids by using a systematic method based on layer potentials. Our computations reveal an underlying elegant relation between the elastic moment tensors and the single layer potential.